Stigma Pada Penderita HIV/AIDS: A Systematic Review - Maulidiah Junnatul Azizah Heru; Atika Jatimi; Mukhlish Hidayat (Universitas Nazhatut Thullab Al- Muafa Sampang, 2023)
Introduction: Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is a virus that attacks the human immune system. Negative stigma in HIV/AIDS patients can affect the level of quality of life of HIV patients, which in turn can affect the patient's psychology, self-confidence, and career. Factors that cause discrimination against PLWHA are the low level of education and public understanding of HIV/AIDS. Objective: to determine the stigma of HIV/AIDS sufferers. Method: The method for preparing this article is the PRISMA method with database searches including Google Scholar, Digital Reference Garba, and Science Direct, using 10 articles based on inclusion criteria, namely published in 2019-2023, can be accessed in full text, articles in Indonesian and English and is research qualitative. Results: Of the 10 articles that have been analyzed, it is stated that stigma in HIV/AIDS sufferers can affect aspects of mental health, especially the quality of life of HIV/AIDS sufferers. The stigma faced by leprosy sufferers is self-stigma and public stigma. Conclusion: The stigma experienced by HIV patients comes from themselves, their families, society, and the surrounding environment. Stigma also causes depression and anxiety, feelings of sadness, guilt, and feelings of lack of worth due to low levels of knowledge about HIV/AIDS